A healthy view? exploring the positive health perceptions of older adults with a lower socioeconomic status using photo-elicitation interviews. Issue 1 (1st January 2021) - Platzer, Feline; Steverink, Nardi; Haan, Marieke; de Greef, Mathieu; Goedendorp, Martine
ABSTRACT: Purpose: The health perceptions of older adults with a lower socioeconomic status still seems to be unsettled. To gain more insight in these perceptions, 19 older adults were interviewed with the use of a photo-elicitation method. Methods: Participants reflected on ten photographs covering aspects of physical, social and mental health, and were also asked if and how they experience to have control over their health. Results: The results showed that the perception of health depended on the background of the participant, was experience-oriented and was mostly focused on the negative aspects of physical and mental health. Social contacts were an important contributor to well-being, especially when physical health declined. Although most participants seem hardly aware of having influence on their own health, several participants showed automatic self-management abilities. Conclusion: For participants who need more support to improve, or become more aware of their self-management abilities, interventions with an experience-oriented approach are needed.